Water-based binder, preparation method thereof and water-based lithium iron phosphate positive electrode slurry
By preparing an aqueous binder containing a dibasic anhydride copolymer and a water-soluble soft emulsion, the problems of existing water-based binders being difficult to disperse and low solid content in the positive electrode material are solved, and the performance and life of the battery are significantly improved.
Patent Information
- Application Number
- CN202411797412.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
AI Technical Summary
The existing water-based binders have problems such as dispersion difficulties, low solid content, material agglomeration, electrode cracking or powder falling off in the use of positive electrode materials, resulting in low specific capacity of the battery and poor cycle life.
An aqueous binder is provided, which includes 25 to 90 parts of the first binder, 10 to 65 parts of the second binder, 2 to 15 parts of the dispersant, and 0 to 5 parts of the auxiliary agent. The first binder is an aqueous solution of dibasic anhydride copolymer, prepared by hydrolysis, crosslinking and neutralization reactions. The second binder is a water-soluble soft emulsion, and the aqueous binder is formed by blending and cross-linking.
The slurry adjustment and coating performance of aqueous lithium iron phosphate is improved, dispersibility, solid content and heat resistance are improved, electrode cracking and powder fall off are avoided, and the reversible capacity, capacity retention and long cycle performance of lithium-ion batteries are enhanced.
Smart Images

Figure BDA0005177156580000091 
Figure BDA0005177156580000101 
Figure HDA0005177156620000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to an aqueous binder and a preparation method thereof, and an aqueous lithium iron phosphate positive electrode slurry. Background Art
[0002] Batteries are an important source of energy for human production and life. With the increasing awareness of environmental protection and energy crisis, as well as the rapid development of mobile electronic devices and electric vehicles, people's demand for energy storage devices is increasing. The rapid development of various energy storage technologies such as lithium-ion batteries, flow batteries, and sodium-ion batteries has made batteries play an increasingly important role in energy fields such as 3C energy storage components, power batteries, and energy storage batteries, which is related to the realization of the "dual carbon" goal process.
[0003] Electrode is the most important component of battery. As a part of electrode, binder is used in small amount but plays a huge role. It plays a bonding role between electrode active material particles and between materials and current collectors. It maintains the stability of electrode during battery use and plays a decisive role in battery performance and safety.
[0004] Lithium iron phosphate positive electrode slurry generally uses polyvinylidene fluoride PVDF as a binder, but the organic solvent methyl pyrrolidone NMP is expensive and not environmentally friendly, which is harmful to the human body and the environment. Water-based binders are environmentally friendly and low-priced, and it is a general trend to replace PVDF, but water-based binders still have many shortcomings in the use of positive electrode materials: such as difficulty in dispersion, low solid content, and material agglomeration during slurry mixing; cracking or powder shedding of electrodes during coating; and low battery specific capacity and poor cycle life in electrical performance tests. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides an aqueous binder and a preparation method thereof, an aqueous lithium iron phosphate positive electrode slurry and a lithium ion battery.
[0006] In order to achieve the above purpose, the technical solution of the present invention is:
[0007] A water-based binder comprises, by weight, 25 to 90 parts of a first binder, 10 to 65 parts of a second binder, 2 to 15 parts of a dispersant and 0 to 5 parts of an auxiliary agent; the first binder is an aqueous solution of a dibasic acid anhydride copolymer, the raw materials of which by weight comprise 60 to 85 parts of a maleic anhydride copolymer, 5 to 15 parts of a cross-linking agent and 10 to 25 parts of an alkali metal hydroxide, the raw materials are mixed with water in a mass ratio of the maleic anhydride copolymer to water of 1:(5 to 20), and the maleic anhydride copolymer is subjected to hydrolysis, cross-linking and neutralization to obtain the binder; the second binder is a water-soluble soft emulsion; the first binder, the second binder and the dispersant are mixed and cross-linked to form the water-based binder.
[0008] Optionally, the water-soluble soft emulsion includes at least one of styrene acrylic emulsion, pure acrylic emulsion, silicone acrylic emulsion, styrene butadiene rubber emulsion, and hydrogenated nitrile butadiene rubber emulsion.
[0009] Optionally, the dispersant includes at least one of polyether-modified styrene-maleic anhydride copolymer, modified styrene-maleic acid copolymer, polystyrene-maleic acid ester, styrene-butadiene anhydride copolymer, polyacrylate, phosphate ester, and alkyl ammonium salt of a copolymer with an acidic group.
[0010] Optionally, the auxiliary agent is lauryl alcohol or hexadecyl alcohol.
[0011] Optionally, the maleic anhydride copolymer comprises at least one of styrene-maleic anhydride copolymer, ethylene-maleic anhydride copolymer, methyl vinyl ether-maleic anhydride copolymer, isobutylene-maleic anhydride copolymer, and acrylic acid-maleic anhydride copolymer.
[0012] Preferably, the molecular weight of the methyl vinyl ether-maleic anhydride copolymer is 300,000 to 2.5 million; more preferably, the molecular weight is 700,000 to 1.5 million.
[0013] Optionally, the cross-linking agent is at least one of polyvinyl alcohol, polyethylene glycol, ethanolamine and triethanolamine.
[0014] Preferably, the molecular weight of polyvinyl alcohol is 10,000 to 250,000; more preferably, the molecular weight is 100,000 to 150,000.
[0015] Optionally, the alkali metal hydroxide comprises at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, magnesium hydroxide, and calcium hydroxide.
[0016] Optionally, the aqueous binder has a solid content of 5% to 20%, a viscosity of 100 to 15000 mPa·s, and a pH of 4 to 10; preferably, the solid content is 10% to 15%, the viscosity is 3000 to 6000 mPa·s, and the pH is 6 to 8.
[0017] A method for preparing the above-mentioned aqueous binder comprises:
[0018] The maleic anhydride copolymer is placed in water, heated at 60-80° C. for hydrolysis, stirred while heating for 1-2 hours, then a crosslinking agent is added, the heating and stirring are continued for 1-2 hours, and an alkali metal hydroxide is added to adjust the pH to obtain a first binder;
[0019] The second binder, dispersant and auxiliary agent are added to the first binder, and the mixture is blended and cross-linked by stirring, ball milling, sand milling, ultrasound or high-speed shearing to prepare the water-based binder.
[0020] Optionally, the stirring speed is 500-2000 rpm.
[0021] A water-based lithium iron phosphate positive electrode slurry comprises, by weight, 90 to 98 parts of active material, 1 to 5 parts of conductive agent and 1 to 5 parts of water-based binder, wherein the water-based binder is the above-mentioned water-based binder.
[0022] Optionally, the active material is lithium iron phosphate after high-temperature treatment, and the high-temperature treatment is performed in an air atmosphere at a temperature of 180 to 220° C. for 1 to 3 hours.
[0023] Furthermore, the conductive agent comprises at least one of SuperP, Ketjen black, acetylene black, carbon nanotubes, nano graphite powder, and graphene.
[0024] The aqueous lithium iron phosphate positive electrode slurry is evenly coated on aluminum foil or carbon-coated aluminum foil, and after drying, a lithium iron phosphate electrode plate is obtained and applied to a lithium ion battery, wherein the maleic anhydride copolymer contains abundant carboxyl groups and has good dispersibility, and is also beneficial to improving the conductivity rate of lithium ions; the water-soluble soft emulsion improves the flexibility of the electrode, the dispersant improves the wettability and uniformity of the material, and the additive further improves the volatilization rate of the solvent to prevent the electrode from cracking.
[0025] The beneficial effects of the present invention are:
[0026] The components of the aqueous binder work synergistically, have the characteristics of good dispersibility, heat stability and electrolyte resistance, and improve the slurry preparation and coating performance of aqueous lithium iron phosphate; the prepared aqueous lithium iron phosphate positive electrode slurry has good dispersibility and high solid content; the dried lithium iron phosphate electrode is tightly bonded to the substrate without cracking and powder peeling, and can be used in lithium-ion batteries to improve the battery's reversible capacity, capacity retention rate and long cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the first cycle charge and discharge curve of Example 1;
[0028] Figure 2 The charge and discharge efficiency and cycle performance (1C) of Example 1, Comparative Example 1 and Comparative Example 3;
[0029] Figure 3 The rate performance of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0030] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments.
[0031] Example 1
[0032] The preparation method of the aqueous binder I applied to the lithium iron phosphate positive electrode material in this embodiment comprises the following steps:
[0033] 1) Weigh 1.2g of methyl vinyl ether-maleic anhydride copolymer powder, add 15.68g of deionized water, heat in a water bath at 80°C, and stir with a magnetic force until the powder is dissolved; add 0.18g of polyvinyl alcohol, continue stirring at a constant temperature of 80°C for 1 hour; add 0.3g of anhydrous lithium hydroxide solid, and stir at room temperature until the solid powder is completely dissolved. The aqueous solution of the first binder is prepared.
[0034] 2) 0.18g of dispersant, 2.4g of second binder and 0.06g of auxiliary agent were added to the first binder in sequence, and stirred evenly to prepare a blended binder. The dispersant was BYK ET3004, the second binder was modified acrylic soft emulsion L-1128 of Xiangrun New Materials, with a solid content of 45%, and the auxiliary agent was lauryl alcohol.
[0035] 3) The mixed binder is stirred magnetically at room temperature and a rotation speed of 2000 rpm for 4 to 6 hours to perform crosslinking and homogenization to obtain an aqueous binder I with a solid matter mass fraction of 15%.
[0036] The above-mentioned aqueous binder I was used to prepare lithium iron phosphate slurry. According to the mass ratio of active substance: carbon black: carbon nanotube: binder = 95:1:1:3, 1.90g lithium iron phosphate, 0.02g conductive carbon black Super P, 0.32g carbon nanotube dispersion with a mass fraction of 6.25%, and 0.4g aqueous binder I were weighed. After adding a certain amount of deionized water, the slurry was prepared.
[0037] The active material is lithium iron phosphate treated at high temperature, and the treatment method is to place it in an oven at 200° C. for 2 hours in an air atmosphere. Unless otherwise specified, the following examples and comparative examples all use lithium iron phosphate treated at high temperature.
[0038] Example 2
[0039] The same as Example 1, except that the lithium iron phosphate used is not subjected to high temperature treatment.
[0040] Example 3
[0041] The preparation method of the aqueous binder II applied to the lithium iron phosphate positive electrode material in this embodiment includes the following steps:
[0042] 1) Weigh 1.0g of methyl vinyl ether-maleic anhydride copolymer powder, add 15.02g of deionized water, heat in a water bath at 80°C, and stir with a magnetic force until the powder is dissolved; add 0.08g of polyvinyl alcohol, continue stirring at a constant temperature of 80°C for 1 hour; add 0.15g of anhydrous lithium hydroxide solid, and stir at room temperature until the solid powder is completely dissolved. The aqueous solution of the first binder is prepared.
[0043] 2) 0.09 g of dispersant, 3.6 g of second binder and 0.06 g of auxiliary agent were added to the first binder in sequence, and stirred evenly to prepare a blended binder. The dispersant was Digo 4100, the second binder was modified acrylic soft emulsion L-1128 of Xiangrun New Materials, with a solid content of 45%, and the auxiliary agent was lauryl alcohol.
[0044] 3) The mixed binder is stirred magnetically at room temperature and a rotation speed of 2000 rpm for 4 to 6 hours to perform crosslinking and homogenization to obtain an aqueous binder II with a solid matter mass fraction of 15%.
[0045] The above-mentioned aqueous binder II is used to prepare lithium iron phosphate slurry. According to the mass ratio of active substance: carbon black: carbon nanotube: binder = 96.5:1:0.5:2, 1.93g of lithium iron phosphate, 0.02g of conductive carbon black Super P, 0.16g of carbon nanotube dispersion with a mass fraction of 6.25%, and 0.27g of aqueous binder II are weighed. After adding a certain amount of deionized water, the slurry is prepared.
[0046] Example 4
[0047] The preparation method of the aqueous binder III applied to the lithium iron phosphate positive electrode material in this embodiment includes the following steps:
[0048] 1) Weigh 1.38g of methyl vinyl ether-maleic anhydride copolymer powder, add 16.12g of deionized water, heat in a water bath at 80°C, and stir with a magnetic force until the powder is dissolved; add 0.24g of polyvinyl alcohol, continue stirring at a constant temperature of 80°C for 1 hour; add 0.45g of anhydrous lithium hydroxide solid, and stir at room temperature until the solid powder is completely dissolved. The aqueous solution of the first binder is prepared.
[0049] 2) 0.15 g of dispersant, 1.6 g of second binder and 0.06 g of auxiliary agent were added to the first binder in sequence and stirred evenly to prepare a blended binder. The dispersant was BYK191, the second binder was modified acrylic soft emulsion L-1128 of Xiangrun New Materials, with a solid content of 45%, and the auxiliary agent was lauryl alcohol.
[0050] 3) The mixed binder is stirred magnetically at room temperature and a rotation speed of 2000 rpm for 4 to 6 hours to perform crosslinking and homogenization to obtain a water-based binder III with a solid matter mass fraction of 15%.
[0051] Use the above-mentioned aqueous binder III to prepare lithium iron phosphate slurry. According to the mass ratio of active substance: carbon black: carbon nanotube: binder = 93.5:1:1.5:4, weigh 1.87g of lithium iron phosphate, 0.02g of conductive carbon black Super P, 0.48g of carbon nanotube dispersion with a mass fraction of 6.25%, and 0.53g of aqueous binder III. After adding a certain amount of deionized water, prepare the slurry.
[0052] Example 5
[0053] The preparation method of the aqueous binder IV applied to the lithium iron phosphate positive electrode material in this embodiment comprises the following steps:
[0054] 1) Weigh 1.10g of methyl vinyl ether-maleic anhydride copolymer powder, add 15.35g of deionized water, heat in a water bath at 80°C, and stir with a magnetic force until the powder is dissolved; add 0.12g of polyvinyl alcohol, continue stirring at a constant temperature of 80°C for 1 hour; add 0.08g of anhydrous magnesium hydroxide solid, stir at room temperature until the solid powder is completely dissolved, then add 0.2g of anhydrous lithium hydroxide solid, and continue stirring until the solid powder is completely dissolved. The aqueous solution of the first binder is prepared.
[0055] 2) 0.15 g of dispersant and 3.0 g of second binder were added to the first binder in sequence, and stirred evenly to prepare a blended binder. The dispersant was BYK ET3004, and the second binder was modified acrylic soft emulsion L-1128 of Xiangrun New Materials, with a solid content of 45%.
[0056] 3) The mixed binder is stirred magnetically at room temperature and a rotation speed of 2000 rpm for 4 to 6 hours to perform crosslinking and homogenization to obtain an aqueous binder IV with a solid matter mass fraction of 15%.
[0057] As in Example 1, lithium iron phosphate slurry was prepared using the aqueous binder IV.
[0058] Example 6
[0059] The preparation method of the aqueous binder V applied to the lithium iron phosphate positive electrode material in this embodiment comprises the following steps:
[0060] 1) Weigh 1.2g of poly(ethylene-alt-maleic anhydride) powder, add 15.68g of deionized water, heat in a water bath at 80°C, and stir with a magnetic force until the powder is dissolved; add 0.18g of polyvinyl alcohol, continue stirring at a constant temperature of 80°C for 1 hour; add 0.3g of anhydrous lithium hydroxide solid, and stir at room temperature until the solid powder is completely dissolved. The aqueous solution of the first binder is prepared.
[0061] 2) 0.18g of dispersant, 2.4g of second binder and 0.06g of auxiliary agent were added to the first binder in sequence, and stirred evenly to prepare a blended binder. The dispersant was BYK ET3004, the second binder was modified acrylic soft emulsion L-1128 of Xiangrun New Materials, with a solid content of 45%, and the auxiliary agent was lauryl alcohol.
[0062] 3) The mixed binder is stirred magnetically at room temperature and a rotation speed of 2000 rpm for 4 to 6 hours to perform crosslinking and homogenization to obtain an aqueous binder V with a solid matter mass fraction of 15%.
[0063] Similar to Example 1, lithium iron phosphate slurry was prepared using the aqueous binder V.
[0064] Example 7
[0065] The preparation method of the aqueous binder VI applied to the lithium iron phosphate positive electrode material in this embodiment comprises the following steps:
[0066] 1) Weigh 1.08g of methyl vinyl ether-maleic anhydride copolymer powder, add 15.68g of deionized water, heat in a water bath at 80°C, and stir with a magnetic force until the powder is dissolved; add 0.12g of polyvinyl alcohol, and continue stirring at a constant temperature of 80°C for 1 hour; add 0.36g of anhydrous lithium hydroxide solid in sequence, stir at room temperature until the solid powder is completely dissolved, then add 0.12g of styrene maleic anhydride copolymer powder, and continue stirring until the solid powder is completely dissolved. The aqueous solution of the first binder is prepared.
[0067] 2) 0.18g of dispersant, 2.4g of second binder and 0.06g of auxiliary agent were added to the first binder in sequence, and stirred evenly to prepare a blended binder. The dispersant was BYK ET3004, the second binder was modified acrylic soft emulsion L-1128 of Xiangrun New Materials, with a solid content of 45%, and the auxiliary agent was lauryl alcohol.
[0068] 3) The mixed binder is stirred magnetically at room temperature and a rotation speed of 2000 rpm for 4 to 6 hours to perform crosslinking and homogenization to obtain an aqueous binder VI with a solid matter mass fraction of 15%.
[0069] As in Example 1, lithium iron phosphate slurry was prepared using the aqueous binder VI.
[0070] Example 8
[0071] The preparation method of the aqueous binder VII applied to the lithium iron phosphate positive electrode material in this embodiment comprises the following steps:
[0072] 1) Weigh 1.2g of methyl vinyl ether-maleic anhydride copolymer powder, add 15.38g of deionized water, heat in a water bath at 80°C, and stir with a magnetic force until the powder is dissolved; add 0.18g of polyvinyl alcohol, continue stirring at a constant temperature of 80°C for 1 hour; add 0.3g of anhydrous lithium hydroxide solid, and stir at room temperature until the solid powder is completely dissolved. The aqueous solution of the first binder is prepared.
[0073] 2) 0.18g of dispersant, 2.7g of second binder and 0.06g of auxiliary agent were added to the first binder in sequence, and stirred evenly to prepare a blended binder. Different from Example 1, the second binder was styrene butadiene rubber latex, model: Japan Zeon BM-451B, with a solid content of 40%.
[0074] 3) The mixed binder is stirred magnetically at room temperature and a rotation speed of 2000 rpm for 4 to 6 hours to perform crosslinking and homogenization to obtain an aqueous binder VII with a solid matter mass fraction of 15%.
[0075] As in Example 1, lithium iron phosphate slurry was prepared using the aqueous binder VII.
[0076] Example 9
[0077] The preparation method of the aqueous binder VIII applied to the lithium iron phosphate positive electrode material in this embodiment comprises the following steps:
[0078] 1) Weigh 1.2g of methyl vinyl ether-maleic anhydride copolymer powder, add 15.68g of deionized water, heat in a water bath at 80°C, and stir with a magnetic force until the powder is dissolved; add 0.18g of polyvinyl alcohol, continue stirring at a constant temperature of 80°C for 1 hour; add 0.3g of anhydrous lithium hydroxide solid, and stir at room temperature until the solid powder is completely dissolved. The aqueous solution of the first binder is prepared.
[0079] 2) 0.18 g of dispersant, 2.4 g of second binder and 0.06 g of auxiliary agent were added to the first binder in sequence and stirred to obtain a blended binder. Different from Example 1, the second binder was a modified acrylate solution, model TEGO 1300, with a solid content of 45%.
[0080] 3) The mixed binder is stirred magnetically at room temperature and a rotation speed of 2000 rpm for 4 to 6 hours to perform crosslinking and homogenization to obtain an aqueous binder VIII with a solid matter mass fraction of 15%.
[0081] As in Example 1, lithium iron phosphate slurry was prepared using the aqueous binder VIII.
[0082] Comparative Example 1
[0083] A PVDF-NMP binder solution with a weight percentage of 5% was prepared, wherein PVDF is a commercially available powder product, model 5130.
[0084] The lithium iron phosphate slurry was prepared using the above 5% PVDF binder, and 1.90g of lithium iron phosphate, 0.02g of conductive carbon black Super P, 0.4g of 5.0% carbon nanotube dispersion, and 1.2g of 5% PVDF solution were weighed according to the mass ratio of active substance: carbon black: carbon nanotube: binder = 95:1:1:3, and a certain amount of NMP solvent was added to prepare the slurry. The lithium iron phosphate was not subjected to high temperature treatment.
[0085] Comparative Example 2
[0086] The same as comparative example 1, except that lithium iron phosphate treated at high temperature is used.
[0087] Comparative Example 3
[0088] Comparative Example 1 is a method for preparing an aqueous binder IX for lithium iron phosphate positive electrode materials. Unlike Example 1, the aqueous binder does not contain a dispersant, and comprises the following steps:
[0089] 1) Weigh 1.2g of methyl vinyl ether-maleic anhydride copolymer powder, add 15.46g of deionized water, heat in a water bath at 80°C, and stir with a magnetic force until the powder is dissolved; add 0.18g of polyvinyl alcohol, continue stirring at a constant temperature of 80°C for 1 hour; add 0.3g of anhydrous lithium hydroxide solid, and stir at room temperature until the solid powder is completely dissolved. The aqueous solution of the first binder is prepared.
[0090] 2) Add 2.8g of the second binder and 0.06g of the auxiliary agent to the first binder in sequence, stir evenly to prepare a blended binder. The dispersant is BYK ET3004, the second binder is Xiangrun New Material's modified acrylic soft emulsion L-1128, with a solid content of 45%, and the auxiliary agent is lauryl alcohol.
[0091] 3) The mixed binder is stirred magnetically at room temperature and a rotation speed of 2000 rpm for 4 to 6 hours to perform crosslinking and homogenization to obtain a water-based binder IX with a solid matter mass fraction of 15%.
[0092] As in Example 1, lithium iron phosphate slurry was prepared using the aqueous binder IX.
[0093] Comparative Example 4
[0094] The commercially available LA133 adhesive product has a solid content of 15%.
[0095] The above-mentioned 15% LA133 binder is used to prepare lithium iron phosphate slurry. According to the mass ratio of active substance: carbon black: carbon nanotube: binder = 95:1:1:3, 1.52g lithium iron phosphate, 0.016g conductive carbon black Super P, 0.256g carbon nanotube dispersion with a mass fraction of 6.25%, and 0.32g LA133 solution with a mass fraction of 15% are weighed, and a certain amount of deionized water is added to prepare the slurry.
[0096] Comparative Example 5
[0097] A water-based binder with a weight percentage of 10% PAALi was prepared.
[0098] The above-mentioned 10% PAALi binder was used to prepare lithium iron phosphate slurry. According to the mass ratio of active substance: carbon black: carbon nanotube: binder = 95:1:1:3, 1.52g lithium iron phosphate, 0.016g conductive carbon black Super P, 0.256g carbon nanotube dispersion with a mass fraction of 6.25%, and 0.48g PAALi solution with a mass fraction of 10% were weighed, and a certain amount of deionized water was added to prepare the slurry.
[0099] In the above embodiment, the lithium iron phosphate slurry is prepared by using a Japanese Thinky deaerator, and the deaerator model is ARE-310. The deaerator slurry mixing process is as follows: mixing at 600 rpm for 1 minute, mixing at 2000 rpm for 15 minutes, defoaming at 2200 rpm for 30 seconds, mixing at 600 rpm for 1 minute, mixing at 2000 rpm for 10 minutes, defoaming at 2200 rpm for 30 seconds, and then the slurry mixing step is terminated to prepare the lithium iron phosphate slurry.
[0100] The lithium iron phosphate slurry prepared above is coated on the carbon-coated aluminum foil with a scraper, and after vacuum drying, a lithium iron phosphate electrode sheet is obtained.
[0101] The lithium iron phosphate electrode was cut into discs with a diameter of 12 mm and assembled into CR2032 button batteries in a glove box with an argon atmosphere. The button battery separator was Celgard2500, and the electrolyte was 1.0M LiPF6 in EC:DMC:EMC=1:1:1vol%with 10.0%FEC, 2.0%VC.
[0102] The assembled button cells were subjected to charge and discharge tests and other performance evaluations.
[0103] The slurry preparation conditions and charge-discharge performances of Examples 1 to 9 and Comparative Examples 1 to 5 were compared.
[0104] Table 1 Slurry solid content and discharge specific capacity of each embodiment and comparative example
[0105]
[0106]
[0107] The solid content of the slurry is calculated based on the fluidity of the prepared lithium iron phosphate slurry, and the ratio of the total solid mass to the total slurry mass is the solid content of the slurry.
[0108] The charge and discharge tests were performed using LAND equipment, model CT3002A.
[0109] Figure 1 This is the first cycle charge and discharge curve of Example 1; Figure 2 The charge and discharge efficiency and cycle performance (1C) of Example 1, Comparative Example 1 and Comparative Example 4; Figure 3 The rate performance of Example 1 and Comparative Example 1. As can be seen from the accompanying drawings and Table 1:
[0110] The lithium iron phosphate after high temperature oxidation treatment improves its surface hydrophilicity, is more conducive to the infiltration and dispersion of powder particles in aqueous solution, and improves the slurry and electrode performance. Therefore, compared with Example 2, the slurry solid content and discharge performance of Example 1 are greatly improved. On the contrary, for the PVDF-NMP oily binder, the dispersion effect of lithium iron phosphate after treatment is even less ideal. Compared with Comparative Example 1, the slurry solid content and discharge performance of Comparative Example 2 are both reduced.
[0111] The dispersant can reduce the viscosity of the slurry and improve the flow characteristics of the slurry through steric stabilization. The use of the dispersant further improves the dispersion performance of lithium iron phosphate, increases the solid content of the slurry, and obtains a more uniform slurry. Compared with the slurry of comparative example 3 without adding a dispersant, the solid content and specific capacity of Example 1 are better than those of comparative example 3.
[0112] The existing aqueous binder for preparing lithium iron phosphate slurry has problems such as poor dispersion effect and low specific capacity. For example, in Comparative Example 4, LA133 plus lithium iron phosphate treated at high temperature is used to prepare slurry, and in Comparative Example 5, PAALi plus lithium iron phosphate slurry treated at high temperature is used to prepare slurry. Both have low solid content and specific capacity. The aqueous binder of the present invention has a special functional group. Through the excellent synergistic effect between the components and the surface treatment of lithium iron phosphate, the problems of difficult dispersion and low solid content of slurry adjustment of aqueous lithium iron phosphate slurry are solved, and the charge and discharge performance of the battery is improved.
[0113] The water-based binder of the present invention is used in the preparation of positive lithium iron phosphate slurry, and its main purpose is to replace the existing oil-based slurry preparation method to solve the environmental protection problem of organic solvents and reduce solvent costs. Compared with comparative example 1, the present invention has excellent performance, good dispersion effect, and specific capacity reaches or even exceeds that of PVDF binder.
[0114] From the above results, it can be seen that the aqueous lithium iron phosphate slurry and the binder used in the present invention not only have low raw material cost and simple preparation process, but also have excellent performance and are expected to replace PVDF.
[0115] The above embodiments are only used to further illustrate an aqueous binder and a preparation method thereof, and an aqueous lithium iron phosphate positive electrode slurry of the present invention, but the present invention is not limited to the embodiments. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention fall within the protection scope of the technical solution of the present invention.
Claims
1. A water-based adhesive, characterized in that: The aqueous binder comprises 25 to 90 parts of a first binder, 10 to 65 parts of a second binder, 2 to 15 parts of a dispersant and 0 to 5 parts of an auxiliary agent in parts by weight; the first binder is an aqueous solution of a dibasic acid anhydride copolymer, the raw materials of which comprise 60 to 85 parts of a maleic anhydride copolymer, 5 to 15 parts of a cross-linking agent and 10 to 25 parts of an alkali metal hydroxide in parts by weight, the raw materials are mixed with water in a mass ratio of the maleic anhydride copolymer to water of 1:(5 to 20), and the maleic anhydride copolymer is obtained after hydrolysis, cross-linking and neutralization reactions; the second binder is a water-soluble soft emulsion; the first binder, the second binder and the dispersant are blended and cross-linked to form the aqueous binder.
2. The aqueous adhesive according to claim 1, characterized in that: The water-soluble soft emulsion includes at least one of styrene-acrylic emulsion, pure acrylic emulsion, silicone-acrylic emulsion, styrene-butadiene rubber emulsion and hydrogenated nitrile-butadiene rubber emulsion.
3. The aqueous adhesive according to claim 1, characterized in that: The dispersant includes at least one of polyether modified styrene-maleic anhydride copolymer, modified styrene-maleic acid copolymer, polystyrene-maleic acid ester, styrene-maleic anhydride copolymer, polyacrylate, phosphate ester, and alkyl ammonium salt of copolymer with acidic group.
4. The aqueous adhesive according to claim 1, characterized in that: The auxiliary agent is lauryl alcohol or hexadecyl alcohol.
5. The aqueous adhesive according to claim 1, characterized in that: The maleic anhydride copolymer comprises at least one of styrene-maleic anhydride copolymer, ethylene-maleic anhydride copolymer, methyl vinyl ether-maleic anhydride copolymer, isobutylene-maleic anhydride copolymer, and acrylic acid-maleic anhydride copolymer.
6. The aqueous adhesive according to claim 1, characterized in that: The cross-linking agent is at least one of polyvinyl alcohol, polyethylene glycol, ethanolamine and triethanolamine.
7. The aqueous adhesive according to claim 1, characterized in that: The alkali metal hydroxide includes at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, magnesium hydroxide and calcium hydroxide.
8. A method for preparing the aqueous binder according to any one of claims 1 to 7, characterized in that: include: The maleic anhydride copolymer is placed in water, heated at 60-80° C. for hydrolysis, stirred while heating for 1-2 hours, then a crosslinking agent is added, the heating and stirring are continued for 1-2 hours, and an alkali metal hydroxide is added to adjust the pH to obtain a first binder; The second binder, dispersant and auxiliary agent are added to the first binder, and the mixture is blended and cross-linked by stirring, ball milling, sand milling, ultrasound or high-speed shearing to prepare the water-based binder.
9. An aqueous lithium iron phosphate positive electrode slurry, characterized in that: The composition comprises 90 to 98 parts of active material, 1 to 5 parts of conductive agent and 1 to 5 parts of aqueous binder in parts by weight, wherein the aqueous binder is the aqueous binder according to any one of claims 1 to 7.
10. The aqueous lithium iron phosphate positive electrode slurry according to claim 9, characterized in that: The active material is lithium iron phosphate after high temperature treatment, and the high temperature treatment is carried out in an air atmosphere at a temperature of 180 to 220° C. for 1 to 3 hours.